5G system design architectural and functional considerations and long term research - Global system for mobile communications; Bulakci, Ömer; Queseth, Olav; Boldi, Mauro (John Wiley & Sons Ltd., 2018)
This book provides a comprehensive overview of the latest research and standardization progress towards the 5th generation (5G) of mobile communications technology and beyond. It covers a wide range of topics from 5G use cases and their requirements, to spectrum, 5G end-to-end (E2E) system architecture including core network (CN), transport network (TN) and radio access network (RAN) architecture, network slicing, security and network management. It further dives into the detailed functional design and the evaluation of different 5G concepts, and provides details on planned trials and pre-commercial deployments across the globe"--Page 4 of cover.